2019
DOI: 10.1021/acs.iecr.9b00820
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Estimation and Nonlinear Model Predictive Control Using Community Detection

Abstract: A combined distributed moving horizon estimation and distributed model predictive control architecture is proposed to address the distributed output−feedback control problem for nonlinear process systems. Community detection based on modularity maximization is used to generate separate optimal decompositions for the estimation and control problems on the basis of suitable graphs. The process of benzene alkylation with ethylene is used as a case study to illustrate the application and computational advantages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…These works also demonstrated computational advantages of community-based decompositions. When state information is not fully available, a state observer is needed to combine with the controller; in this case, Yin & Liu 109 adopted an integrated community detection and stabilizability and observability test procedure, while Pourkargar et al 110 proposed to determine the control-oriented and observation-oriented decompositions (which may not coincide) by community detection in a input-state digraph and a stateoutput digraph, respectively.…”
Section: Modularity-based Decomposition For Distributed Control and Optimizationmentioning
confidence: 99%
“…These works also demonstrated computational advantages of community-based decompositions. When state information is not fully available, a state observer is needed to combine with the controller; in this case, Yin & Liu 109 adopted an integrated community detection and stabilizability and observability test procedure, while Pourkargar et al 110 proposed to determine the control-oriented and observation-oriented decompositions (which may not coincide) by community detection in a input-state digraph and a stateoutput digraph, respectively.…”
Section: Modularity-based Decomposition For Distributed Control and Optimizationmentioning
confidence: 99%
“…The argument behind this measure is that modular organizations that arise in natural systems are nonrandom. This measure is intuitive and has seen many interesting applications; for instance, this measure has been shown to provide a flexible and powerful tool for the analysis and design of control architectures and for the decomposition of large‐scale optimization problems . A powerful generalization of Newman's measure has been proposed in Reference and here it was shown that systems of high modularity are extremum points of a Hamiltonian function.…”
Section: Introductionmentioning
confidence: 98%
“…Real‐world networks are complex and large scale, represent very interacting entities, and generate diverse types of data. Biological networks, 1 power networks, 2 controlled chemical processes, 3‐6 and many others 7‐9 are examples of complex networks. Moreover, modern manufacturing plants are increasingly integrated, 10,11 leading to structural and computational complexities.…”
Section: Introductionmentioning
confidence: 99%